Perceptual-cognitive expertise when refereeing the scrum in rugby union - Moore, L. J.; Harris, D. J.; Sharpe, B. T.; Vine, S. J.; Wilson, M. R. (Journal of Sports Sciences, 2019)
Compared to sports performers, relatively little is known about how sports officials make decisions at a perceptual-cognitive level. Thus, this study examined the decision-making accuracy and gaze behaviour of rugby union referees of varying skill levels while reviewing scrum scenarios. Elite (n = 9) and trainee (n = 9) referees, as well as experienced players (n = 9), made decisions while watching ten projected scrum clips and wearing a mobile eye-tracker. Decision-making accuracy and gaze behaviour were recorded for each scrum. The elite and trainee referees made more accurate decisions than the players, and differences in gaze behavior were observed. The elite and trainee referees displayed lower search rates, spent more time fixating central-pack (i.e., front rows, binds, and contact point) and less time fixating outer-pack (e.g., second rows) and non-pack (e.g., other) locations, and exhibited lower entropy than the players. While search rate failed to predict decision-making accuracy, the time spent fixating central-, outer-, and non-pack locations, as well as entropy, were significant predictors. The findings have implications for training perceptual-cognitive skill among sports officials.